Valproic acid, a histone deacetylase inhibitor, regulates cell proliferation in the adult zebrafish optic tectum. Issue 11 (22nd August 2014) - Dozawa, Miki; Kono, Hiromitsu; Sato, Yuki; Ito, Yoko; Tanaka, Hideomi; Ohshima, Toshio
<x xml:space="preserve">Abstract</x> Background: Valproic acid (VPA) has been used to treat epilepsy and bipolar disorder. Several reports have demonstrated that VPA functions as a histone deacetylase (HDAC) inhibitor. While VPA is known to cause teratogenic changes in the embryonic zebrafish brain, its effects on neural stem cells (NSCs) in both the embryonic and adult zebrafish are not well understood. Results: In this study, we observed a proliferative effect of VPA on NSCs in the embryonic hindbrain. In contrast, VPA reduced cell proliferation in the adult zebrafish optic tectum. Treatment with HDAC inhibitors showed a similar inhibitory effect on cell proliferation in the adult zebrafish optic tectum, suggesting that VPA reduces cell proliferation through HDAC inhibition. Cell cycle progression was also suppressed in the optic tectum of the adult zebrafish brain because of HDAC inhibition. Recent studies have demonstrated that HDAC inhibits the Notch signaling pathway; hence, adult zebrafish were treated with a Notch inhibitor. This increased the number of proliferating cells in the adult zebrafish optic tectum with down‐regulated expression of her4, a target of Notch signaling. Conclusions: These results suggest that VPA inhibits HDAC activity and upregulates Notch signaling to reduce cell proliferation in the optic tectum of adult zebrafish. Developmental Dynamics 243:1401–1415, 2014. © 2014 Wiley Periodicals, Inc.